ANALISIS PENERIMAAN PENGGUNA TERHADAP MANAGEMENT LEARNING SYSTEM VILEP BERBASIS M-LEARNING PADA MAHASISWA JURUSAN GIZI DI POLITEKNIK KESEHATAN PALANGKA RAYA - Juni Ramadhani; Ni Wayan Purnawati (Universitas Pahlawan Tuanku Tambusai, 2021)
Absract â€“ M-Learning (Mobile Learning) can be defined as mobile learning media using mobile devices in universities. The Indonesian Ministry of Health in the field of Center for Health Human Resources Education provides a Learning Management System (LMS), a new learning system using technology for students in the health sector. Likewise, in the Department of Nutrition, Health Polytechnic of Ministry of Health, Palangkaraya, also implements the Virtual Learning Program (VILEP) for teachers and students. This study examined the significance of the effect of student admission from Health Polytechnic of Ministry of Health Palangkaraya by of mobile-based VILEP. This study used a research model to describe the relationship between several variables that affect the acceptance of mobile learning as a new innovation at the Palangkaraya Health Polytechnic. For this reason, this study adopted and modified the model of The Uniï¬ed Theory of Acceptance and Use of Technology (UTAUT) from Mahande and Malago (2016) and acceptance M-Learning as an extended UTAUT variable to determine the influenced factors of M-Learning VILEP acceptance of M-Learning VILEP as a new innovation at the Health Polytechnic of Ministry of Health Palangkaraya. Based on the evaluation results of VILEP M-Learning acceptance model, Effort Expectancy (EF), and Facilitating Condition (FC) have a significant effect on Behavioral Intention (BI), while Behavioral Intention (BI) and Facilitating Condition (FC) have a significant effect on acceptance. M-Learning (MA) VILEP. Students have easy access to VILEP system, supported by the infrastructure of the institution. The main intention and infrastructure encourage students to use VILEP as a learning tool. Keywords: M-Learning (Mobile Learning), Virtual Learning Program (VILEP), The Uniï¬ed Theory of Acceptance and Use of Technology (UTAUT) model.